A social desirability scale for the MMPI-2. Which of the two: Wiggins (WSD) or Edwards (ESD)? - Cristina Tobon; Guadalupe Sanchez; Fernando Jimenez (European Journal of Psychology Applied to Legal Context, 2009)
The objective of this research aims to comparatively analyze the diagnostic accuracy of two social desirability detection scales that have been obtained from the 567 items that comprise the Minnesota Multiphasic Personality Inventory-2 (MMPI-2): Wiggins Wsd Scale and Edwards ESD Scale. The 583 participants (232 men and 351 women) were differentiated into two groups according to their way of answering: Honest response group (N = 310) who replied truthfully following the guidelines of MMPI-2, and simulated response group (N = 273) who were instructed to intentionally and consistently show a positive image of themselves. The results have shown a higher diagnostic accuracy and predictive power, although less reliability (Cronbach's α) for the Wiggins (Wsd) Scale than for Edwards (ESD).